2004
DOI: 10.1080/00224490409552214
|View full text |Cite
|
Sign up to set email alerts
|

Disco clothing, female sexual motivation, and relationship status: Is she dressed to impress?

Abstract: The relationship between a female's clothing choice, sexual motivation, hormone levels, and partnership status (single or not single, partner present or not present) was analyzed in 351 females attending Austrian discotheques. We digitally analyzed clothing choice to determine the amount of skin display, sheerness, and clothing tightness. Participants self-reported sexual motivation, and we assessed estradiol and testosterone levels through saliva sampling. Results show that females are aware of the social sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
84
0
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(94 citation statements)
references
References 29 publications
4
84
0
6
Order By: Relevance
“…That is, across cultures and history, 9 women have perpetually competed with female rivals for the attention of men by trying to enhance their physical attractiveness and sexiness (Buss 1988;Etcoff 1999;Grammer et al 2004), especially through clothing and other fashion apparel (Saad 2007;Tooke and Camire 1991). Given that the potential payoffs associated with attractiveness enhancement are greatest when conception probability is highest, we hypothesized that women at high fertility should be more likely to choose products that enhance their sexiness and appearance.…”
Section: Ovulation and Product Choicementioning
confidence: 99%
“…That is, across cultures and history, 9 women have perpetually competed with female rivals for the attention of men by trying to enhance their physical attractiveness and sexiness (Buss 1988;Etcoff 1999;Grammer et al 2004), especially through clothing and other fashion apparel (Saad 2007;Tooke and Camire 1991). Given that the potential payoffs associated with attractiveness enhancement are greatest when conception probability is highest, we hypothesized that women at high fertility should be more likely to choose products that enhance their sexiness and appearance.…”
Section: Ovulation and Product Choicementioning
confidence: 99%
“…Howeveu, theue aue hints that women tuy to enhance theiu sexual attuactiveness duuing the cycle. A study on moue than 300 women uevealed uelationships between clothing stuategies, sexual motivation, and houmone concentuations (Guammeu et al, 2004). Sheeu clothing (mateuial is veuy light and delicate) and sexual motivation was uelated, wheueas salivauy estuadiol concentuation weue couuobouated with skin display and clothing tightness.…”
Section: Women Advertising During Different Cycle Phasesmentioning
confidence: 99%
“…This may be because clothing style communicates information about om n's mating behaviors and intentions. Grammer, Renninger, and Fischer (2005) found that women who self-reported that they were motivated to attend a nightclub to flirt or to find a partner for sex also tended to wear more semi-transparent clothing. Women make greater efforts to augment their beauty and choose to wear more revealing, fashionable, and red clothing during the fertile phase of the ovulatory cycle (Beall & Tracy, 2013;Durante, Li, & Haselton, 2008;Haselton, Mortezaie, Pillsworth, Bleske-Rechek, & Frederick, 2007), when their sexual desire peaks (e.g.…”
Section: Introductionmentioning
confidence: 99%